Transcatheter aortic valve replacement: Protect the kidneys to protect the patient. Issue 4 (12th March 2019) - Kumar, Vijay; Seth, Ashok
Key Points: Transcatheter aortic valve replacement (TAVR) seems superior to surgical aortic valve replacement (SAVR) for intermediate‐term outcomes in patients with aortic stenosis and moderate to severe chronic kidney disease (CKD). Intermediate‐term mortality and the major adverse cardiac and renal event increase if the renal function worsens soon after TAVR or SAVR. Patient's demographic profile, comorbid conditions, and procedural characteristics influence the clinical outcomes emphasizing the need for careful risk assessment in deciding TAVR versus SAVR in CKD patient.